The impact of ESG, intellectual capital, and leverage on company value - Farah Nur Fauziah; Grahita Chandrarin; Diyah Sukanti Cahyaningsih; Deddy Ahmad Fajar (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2026)
This research aims to investigate how environmental, social, and governance (ESG) elements, financial leverage, and intellectual capital (IC) influence the value of companies recognized as ESG Leaders on the Indonesia Stock Exchange. This study adopts a quantitative methodology, analyzing ESG risk scores and secondary data from the annual reports of ESG Leaders listed on the Indonesia Stock Exchange between 2018 and 2022, comprising 110 observations. Multiple regression analysis is used for analysis. The results reveal that ESG factors do not significantly affect company value, while IC has a positive and significant effect. Meanwhile, financial leverage does not demonstrate a significant influence. Furthermore, the control variable of firm age was found to have a positive and significant effect on company value, whereas firm size had a negative and significant effect on company value. These findings can contribute to shaping, refining, or challenging existing practices by offering insights into how ESG and IC data support decision-making processes, provided users clearly understand their information needs. The uniqueness of this study stems from its targeted examination of ESG Leaders on the Indonesia Stock Exchange and its incorporation of IC, evaluated across five dimensions: human capital, structural capital, capital employed, relational capital, and innovation capital.